2018
DOI: 10.1093/mnrasl/sly121
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a recent nova shell as observed by ALMA

Abstract: High resolution ALMA observations of the recent (2.52 yr old) shell of Nova V5668 Sgr (2015) show a highly structured ionized gas distribution with small (10 15 cm) clumps. These are the smallest structures ever observed in the remnant of a stellar thermonuclear explosion. No extended contiguous emission could be found above the 2.5σ level in our data, while the peak hydrogen densities in the clumps reach 10 6 cm −3 . The millimetre continuum image suggests that large scale structures previously distinguished … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…It is not warranted to claim that mere "clumpiness" can account for all this complexity. While we do of course agree that the ejecta does form clumps of some description, as suggested by imaging of classical nova remnants (such as the ALMA imaging of V5668 Sgr by Diaz et al (2018), though detailed conclusions are hindered by a lack of short UV-spacings), we believe that our data set shows that it is not necessary to invoke clumps in order to explain the complex profiles. Instead, a dynamical model consisting of jets, an accretion disc and a simple shell outflow is sufficient to explain the spectra from the early fading of absorption systems until the late nebular phase.…”
Section: Jets Not Clumps Responsible For H-alpha Spectrasupporting
confidence: 55%
See 1 more Smart Citation
“…It is not warranted to claim that mere "clumpiness" can account for all this complexity. While we do of course agree that the ejecta does form clumps of some description, as suggested by imaging of classical nova remnants (such as the ALMA imaging of V5668 Sgr by Diaz et al (2018), though detailed conclusions are hindered by a lack of short UV-spacings), we believe that our data set shows that it is not necessary to invoke clumps in order to explain the complex profiles. Instead, a dynamical model consisting of jets, an accretion disc and a simple shell outflow is sufficient to explain the spectra from the early fading of absorption systems until the late nebular phase.…”
Section: Jets Not Clumps Responsible For H-alpha Spectrasupporting
confidence: 55%
“…be the source of all the 7 Li in the Milky Way. Diaz et al (2018) discovered structures in ALMA imaging of the ejecta of V5668 Sgr which were the smallest scale of those found in the remnants of any stellar explosion so far, although the veracity of the details of the extended emission depends on UV-plane coverage of the interferometric ALMA observations. Jack et al (2017) performed a detailed identification of four optical spectra of V5668 Sgr and compared their spectroscopy with the light curve to show that certain blue-shifted absorption features moved to slower radial velocities during the multiple rises to maximum (present until ∼+80 d in the light curve of V5668 Sgr in the upper panel of Figure 1), and to faster radial velocities during the decline.…”
Section: Classical Nova V5668 Sgrmentioning
confidence: 88%
“…The optical depth is therefore due to free-free absorption, and changes in opacity mean that the ionization state of the absorbing material must be changing. The spectrum never reaches the canonical α = 2 for free-free absorption, implying that the emission is only partially optically thick-perhaps because the τ ≈ 1 photospheres shrink with frequency as expected in a stellar wind (Panagia & Felli 1975;Wright & Barlow 1975) or because the covering factor of the absorbing screen is substantially smaller than unity (e.g., Diaz et al 2018).…”
Section: Understanding the Synchrotron-dominated Light Curve Of V445 Pupmentioning
confidence: 97%
“…Concomitant with the dust observation, during the period of 170 − 240 days, soft (0.3−1 keV) and hard (2−10 keV) X-ray emission was also detected (Gehrz et al 2018). In later stages of the eruption, ALMA observations showed that the gas was condensed in small (≤ 10 15 cm) clumps in the shell (Diaz et al 2018). All these events make V5668 Sgr an especially interesting target, that can be used to study possible correlations between different time-lapsed processes.…”
Section: Introductionmentioning
confidence: 84%